Biochemical characterisation of Larkinella arboricola (LA) Toll/Interleukin-1 receptor (TIR) domain-containing protein stimulator of interferon genes (STING) (TIR-STING) domain - Koh, Daryl Qian Hao (Nanyang Technological University, 2023)
The cyclic GMP-AMP synthase/Stimulator of Interferon Genes (cGAS-STING) immune signalling route is an evolutionary conserved immune signalling mechanism that is essential for microbial defence. STING, in contract to other innate immunity pathways that rely on immobile cascades of signalling events, is extremely mobile throughout the cell. STING is activated on the endoplasmic reticulum (ER), but it does not signal until it reaches the Golgi, where it is swiftly destroyed by the lysosome. Host factors influence each stage of STING trafficking along the secretory route. In mice and humans, abnormal vesicular trafficking or lysosomal dysfunction triggers an immunological response via STING, which frequently results in tissue disease. Many STING signalling trafficking illnesses appear to have an influence on the central nervous system, resulting in neurodegeneration. As a result, STING trafficking adds a new dimension to immunological signalling, which may have far-reaching repercussions in human illness. The objective of this paper is to investigate the STING activation mechanism, the identification of binding partners which may aid in the modulation of STING activity, and the characterisation of TIR domain-containing adaptor molecule 1/Stimulator of Interferon Genes (TIR-STING) mutations which may contribute to a better understanding of its structure and function, by elucidating the functional importance of certain residues and domains.